Caracterização do transcriptoma e da produção embrionária de espermatozóides sexados por citometria de fluxo ou por gradiente de densidade - Santos, William Jardim de Oliveira [UNESP] (2014)
The procedures for sexing by flow cytometry guarantee the accuracy of 85%, but cause damage in sperm viability leading to lower pregnancy rate after 90 days of pregnancy. The objectives of this study were: 1) to characterize differential gene expression in transcriptome of spermatozoa frozen by conventional method, sexed by density gradient centrifugation, by flow cytometry. 2) Compare blastocyst and cleavageratesproduced in vitro by conventional semen sexed by flow cytometry and by density gradient centrifugation. The experimental groups for semen and embryos were: 1) control group: conventional semen subjected to PercollTM gradient of 45/90% and their embryos produced with this semen, 2) gradientgroup: centrifugation in density gradient and their embryos produced with this semen, 3) cytometry group: semen sexed by flow cytometer, subjected to PercollTMmini gradient 45/90% and their embryos produced with this semen. Total RNA was extracted from sperm (20 x 10 6 cells) and it was possible to extract 400 ngRNA/ 20x10 6 cells/animal or it means, 20 fg of RNA per spermatozoa. However cDNA libraries were not built, probably due a high RNA degradation. The cumulus oocyte complexes (COCs) were classified as grade 1, aspirated from antral follicles with 3-8 mm in diameter, ovariesfromslaughterhouse were used and matured for 18 hours in an incubator at 38.5°C, 100% humidity and atmosphere of 5% of CO2 in air. The matured oocytes are going to be placed in contact with the prepared spermatozoa for fertilization and incubated for 20 hours in 5% CO2 at a temperature of 38.5 °C. Presumptive zygotes are going to be washed three times in SOF (half synthetic oviduct fluid) without FBS and without glucose, cultivated and transferred to plates with four wells containing 500 ul of the same medium used for washing zygotes after fertilization. Embryonic development was evaluated 7-8 days after fertilization. The cleavage and blastocysts rates were ...